Effects of Emergency Contraceptive Methods Education on the Knowledge and Attitudes of the Health Care Staff - F Rahimikian; M Moshrefi; M Mirmohammadali; A Mehran; M Amelvalizadeh (Tehran University of Medical Sciences, 2007)
Background & Objective: According to Iranian national statistics, every year 400 to 500 thousand unwanted pregnancies occur in Iran. The emergency contraceptive methods are easily accessible and affordable for the women of this region. Regarding the important role of health care providers in representing these methods, this study is to determine the knowledge and attitudes of these staff toward required contraceptive methods. Methods & Materials: In this semi-experimental study, 216 health personnel working in south of Tehran health centers were randomly selected. Two 30- minute educational sessions were presented to the staff. The methods of education included face to face, and group discussion. At the end of each session a pamphlet was given to the staff. Data were gathered using a questionnaire before and 2-6 weeks after the education. Statistical analysis was carried out using statistical package for social sciences (SPSS).Results: The results showed that there were significant statistical differences between the knowledge and attitudes (P<0.001) of personnel about the emergency contraceptive methods before and after education. There was no significant relationship between demographic characteristics and attitudes of personnel. There was a significant relationship between sex (P<0.001), educational level (P<0.003), educational major (P<0.001), with knowledge after intervention.Conclusion: Knowledge and attitudes toward emergency contraceptive methods increased significantly after education. This finding reveals the importance of continuous education for health care staff such as midwives and physicians to facilitate successful guidance of their patients towards effective family planning.